2015
DOI: 10.1088/1674-1137/39/6/063101
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of D J (2580), D* J (2650), D J (2740), D* J (2760), D J (3000) and D* J (3000) in the D meson family

Abstract: In this work, we tentatively assign the charmed mesons DJ ( 2771.7 ± 1.7 ± 3.8 66.7 ± 6.6 ± 10.5 2763.3 ± 2.3 ± 2.3 60.9 ± 5.1 ± 3.6. The BaBar collaboration also analyzed the helicity distributions to determine the spin-parity, and tentatively identified the (D(2550),D(2600)) as the 2S doublet (0 − , 1 − ), the D(2750) and D(2760) as the D-wave states. The relevant parameters are presented in Table II, where we also present the possible correspondences among the particles observed by the LHCb and BaBar collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 50 publications
(35 reference statements)
4
39
0
Order By: Relevance
“…In recent years, global H 2 O 2 production has exceeded 3 million tons per annum [1] and is predicted to rise year on year at a rate of approximately 4 % with demand forecast to reach 5.2 million tons per annum by 2020. [2] The principal industries that utilise H 2 O 2 (Figure 1) are the pulp/paper bleaching and textile industries [3][4][5][6] as well as water treatment where it is increasingly superseding chlorine containing oxidants, [7][8][9] primarily due to increasing environmental protection legislation. In particular it is known that H 2 O 2 is able to destroy toxic chemicals present in industrial waste water such as thiocyanate, nitrate and hypochlorite.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, global H 2 O 2 production has exceeded 3 million tons per annum [1] and is predicted to rise year on year at a rate of approximately 4 % with demand forecast to reach 5.2 million tons per annum by 2020. [2] The principal industries that utilise H 2 O 2 (Figure 1) are the pulp/paper bleaching and textile industries [3][4][5][6] as well as water treatment where it is increasingly superseding chlorine containing oxidants, [7][8][9] primarily due to increasing environmental protection legislation. In particular it is known that H 2 O 2 is able to destroy toxic chemicals present in industrial waste water such as thiocyanate, nitrate and hypochlorite.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, a Cr 2 O 3 scale with MnCr 2 O 4 incorporated has been identified. [9] Through the Cr/ Mn-rich scale iron may diffuse into the lower part of the alumina layer along the grain boundaries. [21] On a bare steel surface both chromia scale and Mn sulfides (or mixed Mn/Cr sulfides) would coexist.…”
Section: Time-resolved Changes Of Chemical Composition In the Alumimentioning
confidence: 99%
“…[18] The advantageous affinity of Mn to S and its ability to prevent the steel from formation of other crack initiating metal sulfides (like Cr 2 S 3 and FeS) holds for minor Mn concentration in the alloy only, which also applies for P92 with about 0.5 wt%. In case of 2 wt% Mn in the Fe9Cr-alloy, Yu et al [22] reported the growth of a non-protective iron oxide scale.…”
Section: Time-resolved Changes Of Chemical Composition In the Alumimentioning
confidence: 99%
See 1 more Smart Citation
“…PbS cubes with a hierarchical pyramidal pit on each face have been formed by a facile template-free solvothermal approach [18]. PbS nanowires [19] and nanosheets [20] have been prepared by solvothermal method. PbS microcrystals with a flowershaped structure was prepared in a simple aqueous system using microwave irradiation of Pb 2?…”
Section: Introductionmentioning
confidence: 99%